Nutritional status and dietary pattern of the elderly in Thulamela Municipality of Vhembe District - Selekane A. Motadi; Tshifhiwa Khorommbi; Lungile Maluleke; Anzani Mugware; Lindelani Mushaph (AOSIS, 2022)
Background: Dietary patterns provide comprehensive information about the food consumption habits within a population and how an individual's dietary pattern may change with age. Aim: To evaluate the nutritional status and dietary patterns of the elderly in Thulamela municipality of Vhembe district, Limpopo province. Setting: Study was conducted in Thulamela municipality of Vhembe district, Limpopo province. Methods: This study included 300 elderly people recruited from Thulamela municipality of Vhembe district, Limpopo province. The municipality was randomly selected, and convenience sampling was used to choose elderly people. Body weight and height were measured using standard techniques. Body mass index (BMI) was determined and classified using BMI categories. Data on dietary patterns and dietary intake were collected using a food frequency questionnaire. Results: A total of 300 elderly people from villages participated in the study. About 38.6% of elderly people had a primary education, while 28.1% had a secondary education. The prevalence of underweight, overweight and obesity was 2.0%, 34.0% and 17.0%, respectively. Less than half of the elderly people did not meet the reference intake of energy (p = 0.023). More than half of the elderly people did not meet the reference intake of protein, iron, zinc, potassium, calcium and vitamins B1, B12 and C. It was found that 13.7% of the elderly skipped breakfast every day. About 19.6% of the elderly ate supper sometimes, while 13.7% did not eat supper. Conclusion: The findings of the study revealed that most of the participants ate three main meals a day, with a minority skipping either breakfast or dinner or eating in between meals. The prevalence of underweight was low and that of overweight and obesity was high. Contribution: Poor food choices and physiological changes may reduce the inclusion of food rich in minerals and vitamins in the elderly's diets and prompt the prevalence of malnutrition.